Epidemiological Profile Of Leprosy Patient And Its Co-Relation With Their Treatment Compliance In Rural Area Of Kanpur - Srivastava, Anurag; Srivastava, J P; Saxena, S C; Srivastava, V K; Nigam, Seema (Indian Journal of Community Health, 2004)
Research question: To study the epidemiological profile of Leprosy patients in rural area of Kanpur. To study correlation of epidemiological profile with their treatment compliance Study design : Cross sectional study Setting : Rural area of Kanpur (Chaubaypur, PHC) Participants : All registered patients at Chaubaypur PHC for taking MDT. Study period : One year (Oct, 2003 to October 2004) Statistical Analysis : Chi-square test, percentage Result : From total 63 registered cases, 55.56% were MB and 44.44% were PB cases. Maximum prevalence was found in age group of31- 45 (34.92%), Maximum non-compliant patients were from labour class. Absolute illiterate patients showed Maximum non-compliance (39.68%). Maximum registered case were from social class IV (46. 03%)